INVERSI AMPLITUDE VERSUS OFFSET UNTUK MENGETAHUI PENYEBARAN HIDROKARBON Di LAPANGAN “X” - Muhammad Nur Handoyo; Agus Setyawan; Mualimin Mualimin (Youngster Physics Journal, 2013)
Inversion of AVO (Amplitude Versus Offset) can be used to identify and maping the spread of hydrocarbons on seismic data. The research was conducted on the field "X" TAF layer Talang Akar’s  formation’s  North West Java basin. AVO inversion performed to obtain angle stack, intercept, gradient and fluid factor attribute. The results of the angle stack analysis indicate AVO anomaly in TAF layer’s. Based on the crossplot between the intercept with the gradient, TAFlayer’s included in Class III AVO anomaly. The results of fluid factor analysis showed TAF layer’s has a negative value, that is estimated to have hydrocarbon potential Key words: Amplitude Versus Offset (AVO),angle stack, intercept, gradient, fluid factor.